Efektivitas Rancang Bangun Alat Fiksasi Pada Pemeriksaan Os Femur Di Instalasi Radiologi RSUD H. Padjonga Dg. Ngalle Takalar - A.AR.Rakhmansya Iskandar; Nurbeti Salam; Yusran Basra (Lontara Journal of Health Science and Technology, 2020)
Radiology Fixation Tool is a tool made from a specially designed iron plate which is expected to be able to function which contains a report that can be used by the radiologist who handles patients with a femur pryection examination table for non-cooperative patients. This study was designed to obtain information about os femur fixation design assistance in the Radiology Installation of H. Padjonga Regional Hospital, Ngalle Takalar, to obtain information about fixation devices that are made very effective or effective for tool design, patient care, and required radiographic results. This research was conducted in April - May 2019. The type of this research is Deskritiptif where the population and samples that are the object of this research come from radiology radiographers at RSUD H. Padjonga Dg. Ngalle Takalar as many as 8 respondents Based on the results of data collection using a questionnaire in the Radiology Installation of H. Padjonga Hospital in Ngalle Takalar in terms of the Design Tools Obtained results of 100 percent or according to the excellent category of this tool, it is very easy, easy and easy to use for users. For aspects of the Patient Acceptance aspect, the results are 95 percent or in a very good category. While for the Radiographic Results aspect, the results obtained are 75 percent or in the Good category. Preferably the procurement of radiological fixation devices is a necessity. With a fixation tool, it can reduce image sharpness due to movement / thus helping radiographers to produce high quality photos.